Weighing the Military Option: The Effects of Wartime Conditions on Investments in Human Capital - Brian Duncan; Hani Mansour; Bryson Rintala (Institute for the Study of Labor (IZA), 2016)
Military service is an important vehicle through which young Americans invest in their human capital. Using internal military data, we show that county-level exposure to U.S. combat casualties during the Iraq and Afghanistan wars decreased the supply of new soldiers in that county, and changed the observable characteristics of soldiers who enlisted in that county. Using data from the American Community Survey, we find that exposure to casualties at a young age (17-18) increases the probability of dropping out from high school, and decreases the probability of attaining a college degree. The results suggest that increasing access to higher education and skill training positively impacts the human capital investments of marginal students.
Keywords: I20; I22; I26; J22; 330; military service; training; college aid; human capital